Community Health Worker Intervention in Subsidized Housing: New York City, 2016–2017 - Freeman, Amy L. (Am J Public Health, 2020)
From April 2016 to June 2017, the Health + Housing Project employed four community health workers who engaged residents of two subsidized housing buildings in New York City to address individuals’ broadly defined health needs, including social and economic risk factors. Following the intervention, we observed significant improvements in residents’ food security, ability to pay rent, and connection to primary care. No immediate change was seen in acute health care use or more narrowly defined health outcomes.